The relationship between punctuation marks and the reading processing of high School Students - Almeida, Simone Aparecida (2018)
This paper is the result of an experiment carried out in a Master's research study that investigates whether there is a relationship between prosodic perception and production of the punctuation marks in reading aloud and the comprehension of the text. For this, we manipulated the absence/presence of punctuation marks in the stimulus text, in order to observe the influence of this factor on production and comprehension. The results suggest that the absence of punctuation marks can influence the production of reading aloud and lexical retention, but not the overall comprehension of the text.